Surgically Induced Changes in Gut Microbiome and Hedonic Eating as Related to Weight Loss: Preliminary Findings in Obese Women Undergoing Bariatric Surgery. Issue 8 (October 2017) - Sanmiguel, Claudia P.; Jacobs, Jonathan; Gupta, Arpana; Ju, Tiffany; Stains, Jean; Coveleskie, Kristen; Lagishetty, Venu; Balioukova, Anna; Chen, Yijun; Dutson, Erik; Mayer, Emeran A.; Labus, Jennifer S.
ABSTRACT: Objective: Weight loss surgery results in significant changes in the anatomy, function, and intraluminal environment of the gastrointestinal tract affecting the gut microbiome. Although bariatric surgery results in sustained weight loss, decreased appetite, and hedonic eating, it is unknown whether the surgery-induced alterations in gut microbiota play a role in the observed changes in hedonic eating. We explored the following hypotheses: (1) laparoscopic sleeve gastrectomy (LSG) results in changes in gut microbial composition; (2) alterations in gut microbiota are related to weight loss; (3) alterations in gut microbiome are associated with changes in appetite and hedonic eating. Methods: Eight obese women underwent LSG. Their body mass index, body fat mass, food intake, hunger, hedonic eating scores, and stool samples were obtained at baseline and 1-month postsurgery. 16S ribosomal RNA gene sequencing was performed on stool samples. DESeq2 changes in microbial abundance. Multilevel-sparse partial least squares discriminant analysis was applied to genus-level abundance for discriminative microbial signatures. Results: LSG resulted in significant reductions in body mass index, food intake, and hedonic eating. A microbial signature composed of five bacterial genera discriminated between pre- and postsurgery status. Several bacterial genera were significantly associated with weight loss (Bilophila, q = 3E-05; Faecalibacterium q = 4E-05), lower appetite (Enterococcus, q = 3E-05), and reduced hedonic eating (Akkermansia, q = .037) after surgery. Conclusions: In this preliminary analysis, changes in gut microbial abundance discriminated between pre- and postoperative status. Alterations in gut microbiome were significantly associated with weight loss and with reduced hedonic eating after surgery; however, a larger sample is needed to confirm these findings.